2004
DOI: 10.1111/j.1740-8261.2004.04039.x
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic features of drug‐induced splenic congestion

Abstract: Drug-induced splenic congestion has been reported in dogs secondary to barbiturate administration. This research attempted to verify and quantify size changes associated with drug-induced splenic congestion in dogs. Transverse plane ultrasound images of the spleen in normal dogs were collected to determine the maximum diameter in the minimum dimension prior to, and 15 min after, administration of acepromazine, thiopental, or propofol. Significant splenic enlargement was seen after administration of acepromazin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 8 publications
4
43
0
3
Order By: Relevance
“…Th e data obtained in the study confirm those described by O'Brien, Waller and Osgood (2004), who described splenic dilation after acepromazine administration. Disagreeing with these authors, Baldo et al (2012) found no difference in spleen volume by computed tomography after acepromazine use (0.03 mg/kg).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Th e data obtained in the study confirm those described by O'Brien, Waller and Osgood (2004), who described splenic dilation after acepromazine administration. Disagreeing with these authors, Baldo et al (2012) found no difference in spleen volume by computed tomography after acepromazine use (0.03 mg/kg).…”
Section: Discussionsupporting
confidence: 81%
“…This sequestration can be detrimental to some animals (WILSON; EVANS; CARPENTER, 2004), especially those that are hematological impaired prior to surgery. Mechanism of splenomegaly associated with the acepromazine administration is not known but may be related to the α1-adrenergic blockade leading to smooth muscle relaxation and vasodilatation with consequent passive congestion; these changes allow stretching of the spleen capsule's smooth muscle fibers, with enlargement and the increased number of cells (LANG;EGLEN;HENRY, 1979;O´BRIEN;WALLER;OSGOOD, 2004;PARRY;ANDERSON, 1983;WILSON;EVANS;CARPENTER, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Entretanto, esses fármacos não são seletivos para os receptores dopaminérgicos, interagindo também com receptores alfa-1 adrenérgicos periféricos. O bloqueio de receptores alfa-1 adrenérgicos vasculares resulta em vasodilatação periférica, redução na pressão arterial (MONTEIRO et al, 2007) e aumento da perfusão cutânea (BROCK, 1994) e visceral (O'BRIEN et al, 2004). Foi demonstrado também que a acepromazina reduz o hematócrito em cães, sugerindo o sequestro de células vermelhas no baço com consequente esplenomegalia (LANG et al, 1979;O'BRIEN et al, 2004;MONTEIRO et al, 2007).…”
Section: Introductionunclassified
“…O bloqueio de receptores alfa-1 adrenérgicos vasculares resulta em vasodilatação periférica, redução na pressão arterial (MONTEIRO et al, 2007) e aumento da perfusão cutânea (BROCK, 1994) e visceral (O'BRIEN et al, 2004). Foi demonstrado também que a acepromazina reduz o hematócrito em cães, sugerindo o sequestro de células vermelhas no baço com consequente esplenomegalia (LANG et al, 1979;O'BRIEN et al, 2004;MONTEIRO et al, 2007). Por outro lado, existe pelo menos um estudo na literatura que relata a inexistência de correlação entre as alterações no hematócrito promovidas por agentes anestésicos (incluindo a acepromazina) e o volume do baço (WILSON et al, 2004), sugerindo o sequestro de células vermelhas em outros locais além do baço.…”
Section: Introductionunclassified